Pengaruh Eco-enzym dan Trichoderma sp. Terhadap Intensitas Serangan Nematoda Puru Akar (Meloidogyne spp.) Pada Tanaman Seledri (Apium graveolens L.) - Annisa Yulida; Elly Liestiany; Dewi Fitriyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Plant Pest Organisms (OPT) that often attack celery plants are root knot nematodes (NPA) caused by Meloidogyne spp. which usually attacks the roots of the celery plant, causing the roots of the celery plant to swell. One of the efforts in controlling Plant Pest Organisms (OPT), this study aims to determine the effect of eco-enzymes and Trichoderma sp. in suppressing the intensity of NPA attacks on celery plants. The treatments given in this study were control and four treatments Eco-enzym and Trichoderma sp. This research was conducted for 6 months from seeding to harvest. The results showed that each treatment showed various results in controlling attacks on celery plants. Eco-enzyme and Trichoderma sp. (one time) had the effect of being used as a control against NPA attacks on celery plants because the T4 Eco-enzym (10 ml) and Trichoderma sp. (20gr) with an attack intensity percentage of 2.12%, showed the best results in controlling the level of NPA damage in celery plants.